2002
DOI: 10.1001/archneur.59.8.1304
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Patient Dependence in Alzheimer Disease

Abstract: This study shows the validity of the Dependence Scale and demonstrated that dependency in AD significantly declines with time independent of global cognition and other self-care deficits. The scale is a valuable instrument for outcomes research, efficacy trials, and behavioral research in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 28 publications
1
60
0
Order By: Relevance
“…Turning to the relationship between function and cognition, we found a positive association in the LPA and PNFA groups; however, no such relationship was identified for the AD group. Several other studies have also found similar weak correlations between cognition and ADLs in AD [25,26] which is interesting from the context of drug trials, which focus largely on changes in cognitive performance rather than ADLs -yet we found the greatest change over 12 months was in IADLs. The similarity in the associations between ADLs and ACE-R scores found for PNFA and LPA reflect the predominance of language dysfunction in the two PPA variants and the fact that the ACE-R is heavily dependent upon language abilities.…”
Section: Discussionsupporting
confidence: 78%
“…Turning to the relationship between function and cognition, we found a positive association in the LPA and PNFA groups; however, no such relationship was identified for the AD group. Several other studies have also found similar weak correlations between cognition and ADLs in AD [25,26] which is interesting from the context of drug trials, which focus largely on changes in cognitive performance rather than ADLs -yet we found the greatest change over 12 months was in IADLs. The similarity in the associations between ADLs and ACE-R scores found for PNFA and LPA reflect the predominance of language dysfunction in the two PPA variants and the fact that the ACE-R is heavily dependent upon language abilities.…”
Section: Discussionsupporting
confidence: 78%
“…A comparison of R -squared for Models 1–4, suggests that the DS was the best predictor of informal care costs with the beta coefficient suggesting a 71–73% change in informal care cost with a one unit change in DS. Earlier studies have estimated that the DS worsens by 1 point per year [28]. …”
Section: Discussionmentioning
confidence: 99%
“…The DS comprises 11 dichotomous items (e.g., “Does the patient need to be watched or kept company when awake?”) and two items on a 3-point Likert-type scale (e.g., “Does the patient need reminders or advice to manage chores, do shopping, cooking, play games or handle money?”) Scores range from 0 to 15, with higher scores indicating greater dependence. Psychometric properties range from acceptable to excellent (11,23). …”
Section: Methodsmentioning
confidence: 99%